Le sentiment d'efficacité personnelle et l'apprentissage des langues - Isabelle Puozzo Capron (Recherches en didactique des langues et des cultures)
Self-efficacy, theorized by the Canadian psychologist Bandura, contributes to new perspectives on the pedagogical practices of language learning and teaching. According to Bandura, one of the success factors for linguistic performance is the capacity to perceive the skills we have to use in a precise situation. In language learning, the learner possesses some language knowledge, but it is the choice of appropriate strategies that allows this knowledge to be transformed into skills or performance. The teacher can favour this choice through the design of the tasks proposed to students. In this paper, we illustrate two primary sources of self-efficacy: mastery of experiences and vicarious experiences. In order to assess the potential and limitations of these sources, action research was conducted during a French course in a vocational high school in the Aosta Valley in Italy. The theoretical dimension of this paper is thus enriched by a practical and critical look at this theory.